Diversity of leaf-litter anurans in a fragmented landscape of the Atlantic Plateau of Sao Paulo State, southeastern Brazil - Bruscagin, Roberta Thomaz; Condez, Thais Helena [UNESP]; Dixo, Marianna; Bertoluci, Jaime (Taylor & Francis Ltd, 2014)
Brazil is a tropical country and has the greatest anuran species richness in the world: the Atlantic Forest has roughly half of these species. We contribute to the knowledge of the anurans of the Brazilian Atlantic Plateau, determining the composition of anuran fauna associated with leaf litter in six landscapes, patterns of spatial distribution and levels of similarity among these landscapes and other communities. The sampling by pitfall traps was conducted in Sao Paulo state, at a total of 68 sites distributed among continuous and fragmented landscapes. The anuran fauna of these sites is typical of dense ombrophilous forest, and the composition resembled those of other localities of the Atlantic Forest. A cluster analysis comparing the six landscapes resulted in three main groups (Caucaia + Reserva do Morro Grande; Tapirai + Ribeirao Grande; Fazenda Para so + Parque Estadual Jurupar). In the cluster analysis comparing these faunas to those of other localities, we could not find an effect of geographic distance on the differences in composition among areas.
Keywords: frog; conservation; fragmentation; Atlantic Forest; South America